A novel series of forepaw muscles for mammals observed in the Patagonian weasel Lyncodon patagonicus. Issue 5 (13th July 2016) - Ercoli, Marcos Darío; Álvarez, Alicia
Abstract : The intrinsic autopodial musculature of mammals is composed of a relatively stable number of muscular groups. Here, we present the first myological studies of Lyncodon patagonicus, a South American mustelid that is morphologically and ecologically poorly known. The typical intrinsic muscles of the manus of Lyncodon are similar to those of its sister taxon Galictis, although there exist few variations, including additional subdivisions and relatively more distal insertions in some muscles. A striking feature is the presence of a novel series of forepaw muscles never before described for mammals. These muscles, named here mm. flexores digitorum proprii manus, are represented by a medial and a lateral belly for each digit and are located immediately distal to the mm. flexores breves profundi. They are located distally alongside the tendons of the latter, along the palmar aspect of the phalangeal series, and they insert onto the flexor tubercle of the distal phalanx of each digit. We propose that the incorporation of these muscles in the forepaw musculature of Lyncodon, in addition to some other osteo-myological features, imply a distinctive morpho-functional adaptation to increase the force of flexion and independence of digital movements likely used to grasp prey during hunting. This hypothesis should be confirmed by future ecological and behavioral studies on this species. La musculatura intrínseca del autopodio de los mamíferos está compuesta por un número de grupos musculares relativamente estable. En este trabajo nosotros presentamos el primer estudio miológico de Lyncodon patagonicus, un mustélido de América del Sur pobremente conocido tanto en aspectos morfológicos como ecológicos. Los músculos intrínsecos típicos de la mano de Lyncodon son similares a los presentes en el taxón hermano Galictis, aunque presenta algunas variaciones, incluyendo la presencia de subdivisiones adicionales y algunas inserciones relativamente más distales. Una característica distintiva fue la presencia de una novedosa serie de músculos nunca antes descripta para un mamífero. Estos músculos, aquí denominados mm. flexores digitorum proprii manus, están representados por un vientre medial y uno lateral para cada dígito, ubicados inmediatamente distales a los mm. flexores breves profundi. Distalmente, estos se ubican a los lados de los tendones de estos últimos, en el aspecto palmar de la serie falangeal, insertándose en los tubérculos flexores de las falanges distales de cada dígito. Nosotros proponemos que la incorporación de estos músculos a la musculatura de la mano de Lyncodon, sumado a otras características osteo-miológicas, podría implicar una adaptación morfo-funcional distintiva, posibilitando una mayor fuerza de flexión e independencia en los movimientos digitales, posiblemente utilizada por el taxón durante la manipulación de presas durante la caza. Esta función debe ser confirmada por futuros estudios ecológicos y comportamentales para esta especie.